AGIHAN JENIS TUMBUHAN DAN HUBUNGANNYA DENGAN PASANG SURUT DI HUTAN MANGROVE TELUK BUO KECAMATAN BUNGUS TELUK KABUNG KOTA PADANG - Sari, Defri Novita; Eka Putri, Irma Leilani; Rizki, Rizki (STKIP PGRI Sumbar, 2013)
ABSTRACTÂ Mangrove is a typical tropical and subtropical forest plant, grows along the coast or river estuary and affected by the ebb and ride of the sea. The ebb is a factor that determines the distribution of mangrove forest. Almost all mangrove plants have floating seeds, and this results in its easy dissemination by the water to the back of the forest. The purpose of this study is to comprehend the relationship between type of the plats distribution with the tidal wave if the mangrove forest of Teluk Buo, in the district of Bungus / Teluk Kabung, in the city of Padang . This descriptive study was performed during June-July 2013. Samples were collected from two research transection. In the location two transections were created at the lengths of 160 m and 180 m perpendicular to the shore lines toward the forest. Each transection consisted of 16 and 18 observation plots with the size 10 m by 10 m each, with the distance between transections at 100 m to better represent the forests vegetation. The result shows that in the mangrove forest of Teluk Buo there are seven types of mangrove plats, those are Rhizophora apiculata, Sonneratia caseolaris, Aegiceras corniculatum, Acanthus ilicifolius, Bruguiera gymnorrhiza, Dolichandrone spathacea, dan Hibiscus tiliaceus. The height of ebb-tide waves has big influences on the distribution of the plants types. The distribution successively from the shore line to the back of the forest are Rhizophora apiculata, Sonneratia caseolaris, Aegiceras corniculatum, Bruguiera gymnorrhiza, Dolichandrone spathacea, Acanthus ilicifolius, and Hibiscus tiliaceus. The type with the broadest distribution at the highest tide is Rhizophora apiculata.Â